2012
DOI: 10.12659/pjr.882578
|View full text |Cite
|
Sign up to set email alerts
|

Rola tomografii komputerowej w ilościowej ocenie rozedmy płuc

Abstract: SummaryPulmonary emphysema, together with chronic bronchitis is a part of chronic obstructive pulmonary disease (COPD), which is one of the leading causes of death in the United States and worldwide. There are many methods to diagnose emphysema. Unfortunately many of them, for example pulmonary function tests (PFTs), clinical signs and conventional radiology are able to detect emphysema usually in its late stages when a great portion of lung parenchyma has been already destroyed by the disease. Computed tomogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 43 publications
(51 reference statements)
0
15
0
1
Order By: Relevance
“… 9 QCT in patients with COPD is generally accepted as a robust method, especially for quantifying emphysema. 10 QCT-measured emphysema has been shown to predict mortality 11 and has been linked to lung function decrease. 12 QCT in asthmatic patients has demonstrated tremendous heterogeneity in airway remodeling, showing that change in lumen dimension is an important aspect of proximal airway remodeling 8 and identifying that changes in airway geometry are associated with histologic features of airway remodeling.…”
mentioning
confidence: 99%
“… 9 QCT in patients with COPD is generally accepted as a robust method, especially for quantifying emphysema. 10 QCT-measured emphysema has been shown to predict mortality 11 and has been linked to lung function decrease. 12 QCT in asthmatic patients has demonstrated tremendous heterogeneity in airway remodeling, showing that change in lumen dimension is an important aspect of proximal airway remodeling 8 and identifying that changes in airway geometry are associated with histologic features of airway remodeling.…”
mentioning
confidence: 99%
“…It achieved an error smaller than ten on 90% of our data, yielding a mean error of 3.96 overall. Visual interpretation of X-rays has an accuracy of 77%, and low sensitivity when diagnosing mild to moderate emphysema [12]. Our model was able to make predictions with 85.39% accuracy and reached a maximal mean sensitivity of 78.36% when studying emphysema under the condition that a positive emphysema diagnostic is given at a 5% emphysema percentage threshold, significantly improving the X-ray visual diagnostic technique.…”
Section: Discussionmentioning
confidence: 93%
“…However, our results show that even though our model can correctly predict emphysema percentages below 10%, it tends to underestimate measurements above this threshold. Although our model needs to be improved concerning this aspect, it is important to notice that it obtains very accurate scores of small emphysema percentages (mild disease), which are the values that classic image-based diagnosis methods are unable to recognize [12]. When analyzing the activation maps generated by our model, we observed that the main focus of the CNN was the lungs and the diaphragm, and no attention was paid to osseous structures.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A clinically established measure of pulmonary capillary function is the diffusing capacity for carbon monoxide (CO) which is closely linked to the degree of lung emphysema as quantified by CT scans [4]. On the other hand, patients with diabetes without known lung disease also may show a decreased CO diffusing capacity [5, 6], and impairment of pulmonary function in type I diabetes patients treated with insulin was linked to the quality of metabolic control [7].…”
Section: Introductionmentioning
confidence: 99%